O Ateneu, by Raul Pompéia, and the program of the civic-military schools of the Bolsonaro government: claustrotopic space-time - Cruz, Ana Carolina De Picoli De Souza; Cortina, Arnaldo (Estudos Semióticos, 2022)
This article aims to contribute to the numerous reflections on the directions of Brazilian education. Based on the theory of Discursive Semiotics, through the analysis of time, space and ideology in enunciation and in the enunciate, we present a comparison between the novel O Ateneu, by Raul Pompéia (1888), and the guidelines of the civic-military schools (2019) of the Bolsonaro government. Believing that not only closed spaces imprison, but also (and mainly) discourses have the power to confine, we also seek to analyze how the ideologies of the present reveal vestiges of the past and lead us to question whether we are (re)existing or resisting.